An environmental history of the Cederberg : changing climate, land use and vegetation patterns - Bonora, Daniela Vincenza (Department of Biological Sciences, 2023)
This thesis documents how climate and land use practices have changed in the Cederberg over the last century and how these changes have affected vegetation patterns. Along with a description of the major geological, climatic and vegetation gradients in the study area, changes in rainfall, temperature, A-pan evaporation and fire regimes over the 20th century are analysed from official records. While rainfall has not changed significantly from 1900-2007, the last 30 years have been drier than the mean value. The temperature records show an increase of 1°C since the I 960s; however, A-pan evaporation values have declined significantly over the last 30 years. The fire records suggest an increase in area burnt and in frequency since the mid 1940s. Changes in land use and its impacts on Cederberg landscapes are then assessed through a combination of archival sources, repeat photography and oral history. A zonal theme was adopted to analyse the environment of the Cederberg, and land use and landscape changes of the lowlands, midlands and uplands are examined independently. Results show that the Cederberg lowlands have experienced the largest degree of transformation over the course of the 20th century, primarily as a result of the intensification of agriculture, specifically fruit, vine and potato cultivation. Large areas of the midlands have also been transformed, although to a lesser extent than the lowlands. The midlands have experienced a complex history with changes differing between the northern and southern parts of the Cederberg. Evidence from 17 repeat photograph pairs suggests that the natural vegetation of the northern midlands has witnessed a recovery, with a contraction of traditional forms of farming and an increase in tourism and wine making. The southern midlands, on the other hand, have seen an expansion in agricultural production similar to the trends recorded in the lowlands. In contrast to the lowlands and midlands, human-induced transformation of the Cederberg uplands has been minimal. In this region, the impacts of a changing climate and fire regime are most clearly observed, and best explain the declining populations of the endemic Clanwilliam cedar tree (Widdringfonia cedarbergensis). Evidence from 15 repeat photographs shows that there has been a rapid decline (average of 2.5% per annum) over the last 70 years, and if current rates of decline continue, the species will be extinct in the region within 300 years. An increase in fire frequency is the best explanation for the demise of the cedar, although changes in rainfall, temperature and the impacts of disease deserve further investigation. The results of this thesis are relevant for land owners, agriculturalists, conservationists and the tourism industry, and by using repeat photograph pairs, it provides a richly illustrated account of changes in the region over the last 100 years.